Constructing Knowledge Through Memory: An Ethnographic Perspective on Cultural Recall - Feby Triadi (Universitas Cahaya Prima, 2025)
Memory plays a central role in ethnography, shaping both cultural practice and the interpretation of experiences. This study explores how individual and collective memories influence the understanding of social norms, rituals, and everyday life in a community setting. Data were collected using in-depth interviews, participant observation, and narrative documentation, and analysed thematically to identify patterns in memory recall, narrative construction, and cultural interpretation. Findings suggest that memory functions as a cognitive and social framework that informs both participants’ practices and the ethnographer’s analysis. This study highlights the significance of incorporating memory as an analytic lens in ethnography to better capture the temporal, emotional, and symbolic dimensions of culture.